BPLOM: BPM Level-Oriented Methodology for Incremental Business Process Modeling and Code Generation on Mobile Platforms - Solís-Martínez, Jaime; García-Menéndez, Natalia; Pelayo García-Bustelo, B. Cristina; Cueva Lovelle, Juan Manuel (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
The requirements engineering phase is the departure point for the development process of any kind of computer application, it determines the functionality needed in the working scenario of the program. Although this is a crucial point in application development, as incorrect requirement definition leads to costly error appearance in later stages of the development process, application domain experts’ implication remains minor. In order to correct this scenario, business process modeling notations were introduced to favor business expert implication in this phase, but notation complexity prevents this participation to reach its ideal state. Hence, we promote the definition of a level oriented business process methodology, which encourages the adaptation of the modeling notation to the modeling and technical knowledge shown by the expert. This approach reduces the complexity found by domain experts and enables them to model their processes completely with a level of technical detail directly proportional to their knowledge.
Keywords: business process modeling; BPMN; process transformation; code generation; IJIMAI